INOVASI PERANCANGAN KOTA - Qomarun, Qomarun (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The crowded phenomenon is made in most of the city now. The cities sustainable grow and develop to be metropolitan, and just, megapolitan. It makes the farm field change to be houses, buildings, roads and other public facilities of the city. Such of that growth will affect the land can’t be returned to be farm field (irreversible process). It is the most easy to grow the city horizontally, but the land have its limitedness. This paper explores some city development, especially on the basis of land limitation. It is the responsibility of architectural realm on the , increasing of environment qualities Key words: crowded, irreversible, land, model